The new religious movement in Malaysia : a case study of the unification church - Siti Nor Fadhilah Mohamad Arifin
The discipline of studying New Religious Movements (NRMs) is not a new thing in the field of Religionswissenschaft (science of religion). The emergence of the Unification Church (UC), one form of NRM in Malaysia should be a concern as it has tried to propagate Moon’s doctrines on Muslim communities. This study focuses on the development, doctrines and mission of the UC movement through the role of the National Messiah of Malaysia. This study aims to highlight the effort of the missionaries through a few associations to influence the Muslim communities in Malaysia with their ideologies. This study adopts the qualitative method in gathering as well as analysing data. This method is mainly based on library research, analysis of data, and interviews with the participants of propagations in South Korea. The UC movement emerged from the synthesis of a few religions from Shamanism, Buddhism, Taoism, Confucianism and Christianity, which attracted the attention and interest of the researcher to study this movement in detail. This study found several themes such as peace, love, leadership, and true family are promoted to the Muslim communities to cover their modus operandi. The impacts of the UC movement on the Muslim communities in Malaysia will also be analysed. Finally, this study concludes that every Muslim is responsible in disseminating awareness to the society about the emergence of non-Islamic NRMs in Malaysia.